THE ROLE OF STUDENTS AND TEACHERS IN ENGLISH CLASSES USING THE 2013 CURRICULUM (Language Circle: Journal of Language and Literature, 2016)
This research is about curriculum of 2013. In this thesis, the writer was interested in analyzing the Roles of Students and Teachers in English Classes in Senior High School 2 Ungaran.  The aims of the research were to find out the roles of teachers and students in Senior High School 2 Ungaran, and it was also aimed to identify the constraints in applying the roles of teachers and students in the English classes using in Senior High School 2 Ungaran.  This research design used a descriptive qualitative method. The research results show that the teachers had implemented their roles as facilitator, classroom manager and informant. However, they could not perform their roles as the ideal informant since they had to frequently get involved directly to explain more, particularly in structural and grammatical rules, and the time limitation also prevented them to provide feedback since they frequently could not finish the tasks. The constraints faced by the teachers to apply their roles in the English classes were the complication of the documents, the students with different range of skills, different quality of students’ roles, the time limitation, and dominant Teacher’s Talking Time (TTT).